Effect of using full inversion tillage at pasture renewal on soil and plant cadmium concentrations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management, Massey University, Palmerston North, New Zealand - Peng, Yajun (Massey University, 2021)
Cadmium (Cd) accumulation in New Zealand (NZ) agricultural soils has been recognised as a potential concern for food safety, which can limit the exports of some agricultural products. In NZ, elevated soil Cd concentrations in long-term pastures is mainly because of the historic application of Cd-rich phosphate fertiliser. Similar to the strong vertical stratification of soil organic carbon (SOC), total soil Cd concentration also shows a decreasing trend with soil depth. Recently, one-off full inversion tillage (FIT, or deeper ploughing below 25 cm soil depth) at pasture renewal is being investigated in NZ, due to the potential positive impact of this cultivation method on long-term soil C storage. By burying topsoil under the 10–25 cm soil depth, FIT potentially influences soil Cd vertical stratification, but there is no previous research that quantifies the impacts of this practice on soil and plant Cd. Hence, the aim of the current study was to assess the effect of using FIT at pasture renewal on soil and plant Cd concentrations in two contrasting grazed pasture soils. The current study involved the analysis of Cd in soil and plant samples taken from two on-going field trials in the North Island of NZ (Trial 1: Pallic Soil; Trial 2: Allophanic Soil). At both trial sites, three contrasting tillage treatments (i.e. FIT, shallow tillage-ST and no tillage-NT) were used in spring to establish a summer forage crop (leafy turnip), followed by sowing new ryegrass/white clover pasture in autumn. Soil cores were collected to a soil depth of 40 cm before the establishment of tillage treatments (i.e. pre-tillage: PT) and again at the end of the grazing of leafy turnip (i.e. post-tillage: FIT, ST and NT). Changes in soil total Cd (0–40 cm soil depth) and extractable Cd (0–15 cm soil depth) concentrations and soil pH (0–15 cm soil depth) were analysed. In addition, Cd concentration in herbage samples was monitored during both the summer crop and early new pasture growth phases. At both trial sites, FIT modified the vertical stratification of total soil Cd, thus helping reduce topsoil (0–5 cm soil depth) Cd concentration, without changing the total mass of soil Cd to 40 cm soil depth. However, the extent of its effect was different between the two field trials, which was influenced by the pre-tillage total soil Cd concentrations, and its degree of vertical stratification above the 25 cm soil depth. At the Trial 1 site, average total soil Cd concentration in the 0–5 cm soil depth for the FIT treatment was about 24% lower (0.16 mg Cd/kg) than the pre-tillage value (0.21 mg Cd/kg); however, at the Trial 2 site, the average total soil Cd concentration in this soil depth for the FIT treatment was about 40% lower (0.25 mg Cd/kg) than the pre-tillage value (0.42 mg Cd/kg). In terms of extractable Cd concentration, FIT also resulted in a different influence between the two trial sites, because of the contrasting pre-tillage extractable Cd distribution with soil depth. At the Trial 1 site, the FIT treatment had about 52% higher (0.024 mg Cd/kg) average extractable Cd concentration in the 0–5 cm soil depth than the pre-tillage value (0.016 mg Cd/kg), while it had about 57% lower (0.013 mg Cd/kg) average extractable Cd in this soil depth at the Trial 2 site than the pre-tillage value (0.031 mg Cd/kg). Tillage treatments caused contrasting effects on plant Cd concentrations between the two trial sites. In addition, there was also a strong plant species influence on herbage Cd concentrations. In general, the new pasture Cd concentrations were less than 10% of the summer turnip crop at both trial sites. At the Trial 1 site, tillage practices did not significantly (P > 0.05) affect tissue Cd concentrations in either turnip leaves (on average: 0.92, 0.79 and 0.95 mg Cd/kg DM for the FIT, ST and NT treatment, respectively) or new grass (on average: 0.05 mg Cd/kg DM for all tillage treatments). In contrast, at the Trial 2 site, the FIT treatment resulted in lower Cd concentrations for both summer forage crop (on average: 0.69, 0.76 and 0.80 mg Cd/kg DM for the FIT, ST and NT treatment, respectively) and new pasture (on average: 0.04, 0.06 and 0.05 mg Cd/kg DM for the FIT, ST and NT treatment, respectively). Lower Cd uptake by plants sampled for the FIT treatment is likely to be the result of FIT-induced lower total soil Cd and extractable Cd concentrations in the topsoil at this trial site. This field study demonstrated that the use of FIT during pasture renewal can be effective at decreasing total topsoil Cd concentrations in NZ pasture soils, particularly in those soils where there is a high degree of stratification in total soil Cd with soil depth. However, other management practices may also further reduce soil Cd bioavailability after tillage. In particular, any future accumulation of soil organic matter under the new pasture is expected to improve the topsoil’s capacity to bind and immobilise Cd. Further work is required to evaluate the long-term influence of tillage treatments on soil chemical properties (e.g. soil Cd, organic matter and pH), and their effects on Cd bioavailability and uptake by plants.
Keywords: 300204 Agricultural management of nutrients